Skin temperature of middle distance runners after a maximum effort test (Acta Scientiarum. Health Sciences, 2020)
The purpose of this study was to analyze skin temperature (Tsk) responses after a short-term maximum effort test in middle-distance runners. A quasi-experimental study was conducted with ten men (age 23.5±5.10 years) who trained 5 days per week, 2 to 3 hours per day, and were submitted to thermographic evaluation before and after Cooper's 12-minute run test (CRT). The mean temperature of the anterior-superior, posterior-superior, anterior-inferior, and posterior-inferior regions was compared between the sides (i.e., left and right) before and after CRT. The paired t-test showed a significant decrease in Tsk after CRT in the following regions: right pectoralis major (-3.4%), left pectoralis major (-3.4%), and abdomen (-5%) in the anterior-superior view (p